Faktor-Faktor yang Berhubungan dengan Pemberian ASI Ekslusif pada Ibu - Rizki Rahmawati Lestari (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2018)
Pursuant to report result Research Into The Elementary Health (RISKESDAS) 2010 indicating that baby getting ASI ekslusif in Indonesia only 15,3%, while goals of national of coverage of gift of ASI ekslusif of equal to 80%. This research aim to know the education, knowledge, work, age and information from health worker with the gift of ASI Ekslusif. this Desain Research is analytic survey with the approach of cross sectional. Population in this research is Mother having age baby 6-11 month in the Village Petapahan in The Area of Tapung Maintenance Health Center of March period 2013. Technique of Intake sampel is simple random sampling that is as much 56 people. This research is conducted at date of 21-24 June 2013, with the research instrument in the form of kuisioner. Analyse the data used by is Univariat and Bivariate, by using Test of Chi-Square and Yet Correction. Result of research got by frequency of gift of ASI Ekslusif in the Village Petapahan in The Area of Tapung Maintenance Health Center of equal to 41%. P Value of each variable is 0,002, 0,008, 0,758, 0,064 and 0,001. Variable of which deal with gift of ASI Ekslusif that is education, knowledge and information from health worker. While variable which do not correlate is work and mother age .